Rhizosphere effect has no effect on marker genes related to autotrophic CO2 fixation in paddy soils? - Xiao, Ke-Qing; Nie, San-An; Bao, Peng; Wang, Feng-Hua; Bao, Qiong-Li; Zhu, Yong-Guan (Journal of soils and sediments, 2014)
Purpose The rhizosphere is a hotspot for microbial activities as well as microbial ecology studies. This study aimed to explore the “rhizosphere effect” on marker genes of CO 2 fixation autotrophic microorganisms. Materials and methods Microcosm experiments were conducted using two different types of paddy soil, planted with rice and added with urea. At tillering and ripening stages, bulk and rhizosphere soils were sampled separately for DNA extraction and quantitative PCR analyses. Results and discussion Six marker genes ( cbbL G, cbbL R, cbbM , aclB , oorA , accA ) of three autotrophic pathways (the Calvin cycle, the reductive tricarboxylic acid cycle, and the 4-hydroxybutyrate cycle) were detected, suggesting their pervasiveness in paddy soil. Redundancy analysis and variation partitioning based on partial redundancy analysis revealed higher contributions of growth stage (explaining 37 %) and soil type (explaining 19 %) on the variation of these genes, lower but significant impact of rhizosphere effect (explaining 12 %), and no significant effect of urea addition ( P > 0.05). Conclusions These results suggested that the composition of CO 2 fixation autotrophic microorganisms in the paddy soil was subject to combined actions of soil type and growth stage as well as rhizosphere effect.